Maternal and perinatal outcomes of teenage pregnancies: A case control study - M. Zwain , Zainab (Zanco Journal of Medical Sciences (ZJMS), 2025)
Background and objective: Teenage pregnancies are widely distributed in developing countries. Different adverse outcomes are reported for early marriage and teenage pregnancy. This study aimed to assess the maternal and neonatal outcomes of teenage pregnancy in Erbil city-Kurdistan region/Iraq. Methods: From January 1 to June 30, 2024, 200 delivered women were participants of a case-control study at the Maternity Teaching Hospital in Erbil, Kurdistan region, Iraq. Of the 200 women, 100 were teenage cases and the remaining 100 were adult control participants. Both groups’ maternal and perinatal outcomes were assessed. Results: There was a significant difference between the teenage and adult delivered women in relation to age, body mass index, parity, miscarriage history and educational level. Intrauterine growth restriction and emergency cesarean section were significantly different. Gestational diabetes and preeclampsia were more prevalent in teenage pregnancies. Preterm labor, low birth weight and low APGAR scores after 1 and 5 minutes were more in teenage deliveries. Conclusion: Teenage pregnancy is more likely to be accompanied by multiple adverse maternal and neonatal outcomes.